Autoclaved Aerated Concrete (AAC) blocks for wall element at Pejabat Kesihatan Daerah Jeli, Kelantan / Alif Ikmal Mat Izman - Mat Izman, Alif Ikmal (Universiti Teknologi MARA, Perak, 2019)
A good choice material is important especially when it comes to construction industry. A good material used will lead to a strong, high quality, durable, eco-friendly and thermal resistant product such as application of wall that will need to be strong and steady. Hence, this report will discuss mainly about the advantages of material that has been used nowadays which is Autoclaved Aerated Concrete (AAC) that were applied to the construction project under NH Aries SDN BHD titled as "Construction of Pejabat Kesihatan Daerah Jeli, Kelantan". The objectives of this report are to analyse the product material and machineries involved, to observe the laying of Autoclaved Aerated Concrete (AAC) blocks and to determine the advantages of AAC blocks used in the construction industry. For the conclusion of this report, it will explain about the reasons why most of construction nowadays prefer to use these blocks and the solutions of the problems faced during installation.